Human Chorionic Gonadotropin Influences Systemic Autoimmune Responses - De, Alpana; Sachdeva, Ruchi; Bose, Anjali; Malik, Monika; Jayachandran, Nipun; Pal, Rahul (Frontiers in Endocrinology, 2018)
Immunopathological outcomes in Systemic Lupus Erythematosus (SLE; or lupus) are believed to be autoantibody-mediated. Conditions which promote a Th2 skew (such as pregnancy) should encourage antibody production, worsening antibody-mediated diseases while ameliorating Th1/Th17-mediated diseases. Although an increased propensity toward autoreactivity can be observed in pregnant lupus patients and in pregnant lupus-prone mice, whether a unique human pregnancy-specific factor can contribute to such effects is unknown. This study assessed whether human chorionic gonadotropin (hCG, a pregnancy-specific hormone of diverse function) at physiological concentrations could mediate stimulatory influences on immune parameters in non-pregnant, lupus-prone mice, in light of the hormone's ameliorating effects on Th1-mediated autoimmunity in murine models. Results demonstrate that administration of hCG heightened global autoreactivity in such mice; antibodies to dsDNA, RNP68, Protein S, Protein C, β2-glycoprotein 1, and several phospholipids were enhanced, and hormone administration had adverse effects on animal survival. Specifically in splenic cell cultures containing cells derived from lupus-prone mice, hCG demonstrated synergistic effects with TLR ligands (up-modulation of costimulatory markers on B cells) as well as with TCR stimuli (enhanced proliferative responses, enhanced levels of cytokines, and the phosphorylation of p38). In both instances, enhanced synthesis of lupus-associated cytokines was observed, in addition to the heightened generation of autoantibodies reactive toward apoptotic blebs. These results suggest that selective transducive, proliferative, and differentiative effects of hCG on adaptive immune cells may drive autoreactive responses in a lupus environment, and may also potentially provide insights into the association between the presence of higher hCG levels (or the administration of hCG) with the presence (or appearance) of humoral autoimmunity.